How rude! : the teenagers' guide to good manners, proper behavior, and not grossing people out - Packer, Alex J. (Free Spirit Pub., 1997)
A humorous but practical guide to good manners and social skills, discussing such areas as family life, behavior in public, manners in school, eating, and clothes.